A study of current working practices for refrigerant recovery during HVAC maintenance work at Hospital Raja Permaisuri Bainun. - Mohd Hazarudin, Muhammad Haziq Zikry; Mohd Dzulkifli, Syahrun Neizam; Kasmu, Rusdi (Progress in Engineering Application and Technology, 2023)
Compliance with international agreements and regulations aimed at lowering emissions of gases with a high global warming potential (GWP) demands the participation of all stakeholders in the value chain of refrigerant-containing equipment. This study evaluates the current practises for refrigerant recovery during HVAC maintenance work at Hospital Raja Permaisuri Bainun in Ipoh, Malaysia. Edgenta Mediserve technicians responsible for the installation, maintenance, and disassembly of refrigeration equipment are lack of awareness and knowledge related refrigerant recovery. This research presents the survey results of a questionnaires distributed to 20 Edgenta Mediserve technicians in order to evaluate their behaviour, knowledge, and understanding of hazard in relation to refrigerant gases and global warming. Based on the survey and interview results, clearly that technician behaviour and lack of information regarding applicable laws and regulations can significantly contribute to refrigerant emissions. In addition to technical information and training, technicians’ awareness of the effects of refrigerant on global warming is essential for refrigerant-related act, regulations, and initiatives. There are needs to implement information or awareness campaigns more efficiently and dependably and to improve the training of these professionals in key respect-related areas, such as the relationship between greenhouse gases and climate change and the significance of individual accountability. Employers must also implement policies and procedures to ensure compliance with applicable laws and regulations. The study recommends the implementation of training programmes and the development of policies and procedures for the handling of refrigerants in order to improve worker proficiency and reduce the risk of environmental damage.